(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Diabetes mellitus (DM) increases the risk of developing tuberculosis (TB) three-fold. The cost of accessing care for TB-DM co-morbidity poses a significant burden on patients, as they bear both direct and indirect costs of treatment, mostly of out-of-pocket. Objective: To estimate the direct medical cost of illness in patients with TB-DM co-morbidity in two chest clinics in Lagos State. Materials and Methods: An observational study, carried out in two chest clinics in Lagos State to evaluate direct medical costs associated with TBDM co-morbidity during TB treatment. A semi structured questionnaire, pharmacy price list of drugs and an online transportation service lara.ng was employed to document and quantify prescribed medications, laboratory investigations, number of clinic attendance and attendant transportation costs. Results: Among the participants, 53.8% were females. The mean age was 50.7±9.7 years. The total direct medical and non-medical costs for TBDM management was NGN8,604,819 (USD24,585.20) for the duration of TB treatment. Average cost per patient (CPP) was NGN179,384.85 (USD512.53). This was equivalent to 49.8% of the current national minimum wage. Male patients incurred more mean direct medical cost than female patients (NGN26, 647.90 vs NGN24, 020.40), while female patients incurred more mean direct non-medical costs than the males (NGN22, 314.30 versus NGN13, 041.70). Patients aged 60 years and above incurred the highest mean direct costs compared to other age groups. Conclusion: Direct medical costs are substantial in TBDM co-morbidity and increase with age.